Physical Education and Leisure Time Activities Among Pupils With and Without Hearing Loss - Aneta Změlíková; Petra Kurková (OVS LLC, 2021)
The objective of this study was to analyse differences among Czech pupils' with/without hearing loss related to feelings and opinions on physical education classes; sport preferences in physical education classes; and leisure time activities at the lower secondary schools for the deaf.  Materials and methods. Participants were 83 pupils with hearing loss (n = 41; 49.4%) and pupils without hearing loss (n = 42; 50.6%); an average age of them was 14.3 ± 1.3 years. The non-parametric Mann-Whitney U-test, Fisher exact test, Chi-square test were used for statistical analyses. For calculation of effect size coefficient abs(r) was used. All tests were performed at a level of 0.05.  Results. Pupils without hearing loss are more likely to express disappointment due to cancellation of a physical education class than pupils without hearing loss (Z = -2.168; p = 0.029). A statistically significant difference was found in preference for the various physical education activities and in leisure activities, where pupils without hearing loss prefer dancing (χ2 = 8.622; p = 0.003), whereas pupils with hearing loss prefer volleyball (χ2 = 14.833; p = 0.00001). In terms of leisure time activities, pupils with hearing loss spent their leisure time watching television significantly more often (χ2 = 5.198; p = 0.023).  Conclusion. Both groups do not differ in feelings and opinions on physical education in terms of popularity, difficulty, importance, effort during physical education. On the contrary, differences in feelings associated with the cancellation of physical education or preference of activities in physical activities in physical education and leisure time appeared.